Clinical profiling of specific diagnostic subgroups of women with chronic pelvic pain - Demetriou, Lysia; Krassowski, Michal; Abreu Mendes, Pedro; Garbutt, Kurtis; Vitonis, Allison F.; Wilkins, Elizabeth; Coxon, Lydia; Arendt-Nielsen, Lars; Aziz, Qasim; Birch, Judy; Horne, Andrew W.; Hoffman, Anja; et al. (Frontiers in Reproductive Health, 2023)
Introduction Chronic pelvic pain (CPP) is a common condition affecting up to 26.6% of women, with many suffering for several years before diagnosis and/or treatment. Its clinical presentation is varied and there are frequently comorbid conditions both within and outside the pelvis. We aim to explore whether specific subgroups of women with CPP report different clinical symptoms and differing impact of pain on their quality of life (QoL). Methods The study is part of the Translational Research in Pelvic Pain (TRiPP) project which is a cross-sectional observational cohort study. The study includes 769 female participants of reproductive age who completed an extensive set of questions derived from standardised WERF EPHect questionnaires. Within this population we defined a control group (reporting no pelvic pain, no bladder pain syndrome, and no endometriosis diagnosis, N = 230) and four pain groups: endometriosis-associated pain (EAP, N = 237), interstitial cystitis/bladder pain syndrome (BPS, N = 72), comorbid endometriosis-associated pain and BPS (EABP, N = 120), and pelvic pain only (PP, N = 127). Results Clinical profiles of women with CPP (13–50 years old) show variability of clinical symptoms. The EAP and EABP groups scored higher than the PP group (p < 0.001) on the pain intensity scales for non-cyclical pelvic pain and higher than both the BPS and PP groups (p < 0.001) on the dysmenorrhoea scale. The EABP group also had significantly higher scores for dyspareunia (p < 0.001), even though more than 50% of sexually active participants in each pain group reported interrupting and/or avoiding sexual intercourse due to pain in the last 12 months. Scores for the QoL questionnaire (SF-36) reveal that CPP patients had significantly lower QoL across all SF-36 subscales (p < 0.001). Significant effects were also observed between the pain groups for pain interference with their work (p < 0.001) and daily lives (p < 0.001), with the EABP suffering more compared to the EAP and PP groups (p < 0.001). Discussion Our results demonstrate the negative impact that chronic pain has on CPP patients' QoL and reveal an increased negative impact of pain on the comorbid EABP group. Furthermore, it demonstrates the importance of dyspareunia in women with CPP. Overall, our results demonstrate the need for further exploration of interventions targeting QoL more broadly and suggest that novel approaches to classifying women with CPP are needed.